DAYA TARIK MUSEUM TB SILALAHI CENTER KECAMATAN BALIGE KABUPATEN TOBA SAMOSIR PROVINSI SUMATERA UTARA - Ita Foryana Sari Manurung; Syofiah Achnes (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
The attraction is the ability to attract attention. So that the attraction of the museum is the museum's ability to attract the attention of visitors. This study aims to determine the ratings visitor attractions TB Silalahi Center Museum in Toba Samosir, North Sumatra.This research uses descriptive quantitative method to examine the issue in the lift. The sample in this study were 100 respondents, taken using accidental sampling. While data collection techniques in this study using observation, interview, questioner, documentation, and literature study. By using a Likert scale as a measure to determine the length of the short interval.From the results of research conducted in the field with the theory of attraction of the museum is based on components of the museum consists of five sub-variables, namely, appearance, current patterns, exhibitions, attractions reinforcement, and support facilities, then the results of the field in the can that assessment of visitors to attractions TB Silalahi Center Museum are included in the category of Good.Keywords : Tourist attraction, TB Silalahi Center Museum.